An Evaluation of EFL Textbooks Entitled “New Access English for Academic Purposes” for Undergraduate Students - Imam Fauzi (Universitas Muhammadiyah Tangerang, 2019)
The present study is a case specific attempt to explore the effectiveness of English as a foreign language textbooks entitled New Access English for Academic Purposes Revised Edition on the students active learning in EFL situation. The current research underpinned an indepth approach which led to descriptive analysis data collection through a textbook evaluation checklist. It was addressed to 40 undergraduate students in EFL classroom. Textbook evaluation checklist was built on both close and open-ended questions which were comprehensively analyzed separately. The findings revealed that the textbook contributes much advantages on the students active learning, be able to stimulate students in the EFL learning situations, and assist the EFL teachers or lecturers in designing sistematically their classroom learning activities based on the learning objectives and expectation written in the textbook. As explained in the findings of research that some students feel encouraged in terms of utilizing the designed textbook in the language classroom, they thought the EFL textbook is able to improve their English language skills especially in reading, listening, writing, speaking and grammar understanding. Although in the other side, the EFL learners responded that there would be better if the author of textbook tried to make some need analysis for improving and formulating much better language learning materials. Additionally, the EFL lecturers feel assisted after using the textbook for EFL students to construct effectively their course syllabus and language learning activities in the classroom.